Cupping Therapy Combined with Rehabilitation for the Treatment of Radial Palsy: a Case Report - Ali Ramazan Benli; Demir Yazici Senay; Mustafa Koroglu; Tansel Mutlu; Selman Erturhan; Muhammet Nur Ogun; Didem Sunay (MEDrang Inc., 2018)
This case report demonstrates the beneficial effects of cupping therapy (CT) in a 35-year-old man who is diagnosed with a fracture of the radial shaft due to a motorcycle accident. One year after the treatment started, pseudoarthrosis developed in the radius and an autogenous iliac bone graft was performed. However, extension dysfunction in the wrist became evident. After another 6 months of physical therapy and rehabilitation, no improvements were observed. Therefore, CT and adjunctive electrostimulation were performed, after 30 days of treatment, marked recovery of muscle function and full wrist extension were observed, as determined by electromyography and a grade 5/5 on the Medical Research Council power of wrist extension scale. The results in this case study suggest that CT in conjunction with adjunctive electrostimulation, may accelerate functional recovery from postoperative radial palsy, and provide a useful alternative treatment in this situation.